Unified non-local relativistic theory of transport processes - Alexeev, Boris V. (Elsevier, 2016)
Unified Non-Local Relativistic Theory of Transport Processes highlights the most significant features of non-local relativistic theory, which is a highly effective tool for solving many physical problems in areas where the classical local theory runs into difficulties. The book provides the fundamental science behind new non-local physics - generalized for relativistic cases and applied in a range of scales - from transport phenomena in massless physical systems to unified theory of dissipative structures. The book complements the author's previous monograph on Unified Non-Local Theory of Transport Processes (Elsevier, 2015), which is mainly devoted to non-relativistic non-local physics. Nevertheless, the theory as handled in this new work is outlined independently so the book can be studied on its own. Comprehensive collection of non-local relativistic theory with examples that could previously only be found scattered in the literature Provides applications in quantum non-local relativistic hydrodynamics, quantum solitons in solid matter, and plasmas Uses generalized non-local kinetic theory as a highly effective tool for solving many physical problems beyond classical physics Presents non-local relativistic physics in many related problems of hydrodynamics, gravity, nonlinear optics, time quantization, and applied mathematics Includes concrete mathematical problems that are physically consistent and can be solved and studied both analytically and numerically.